Elite U17 football players` physical parameters: focus on contextual variables during training and matches - Kádár, L.; Révész, L.; Sáfár, S.; Géczi, G.; Bognár, J.; Csáki, I. (International Journal of Performance Analysis in Sport, 2025)
The aim of the study was to examine the distribution of training load in relation to the match location, the opponent`s level and the result of the game amongst U17 hungarian elite youth football players. Data was measured with Catapult Vector S7 GPS technology throughout 13 weeks, during the 2022-2023 season (January-June). We measured six volume and six intensity variables, which were analysed depending on the number of days before a match day (MD). The results show that the volume and intensity are significantly higher on MD-4 (e.g. four days before the match) and MD-2 than on MD-1 and MD-5 sessions. Before home games, on MD-5 the players performed better within all of the volume variables than before away games. Before a winning game the intensity of MD-1 training day was lower (TD (m/min), HSR (m/min), TPL (au/min)) than before a lost game. The intensity on MD-2 training day when preparing for a weaker opponent was significantly more intensive (TD (m/min), ACC (count/min), DEC (count/min)) than when it came to a stronger opponent. The examined academy U17 players don`t yet achieve absolute and relative volume and intensity of trainings and matches as previously reported for adult players.